Symbols of Power: Figurative Aspects of Esarhaddon's Babylonian Policy (681-669 B.C.) - Porter, Barbara Nevling (1987)
Ph.D. Dissertation; Supervisors: Tzvi Abusch and J. D. Muhly. - University Microfilms Order No. DA8714110; I. The Years of Preparation. II. Babylonia at the Beginning of Esarhaddon's Reign. III. Gifts and Public Works Projects in Babylonia and Assyria. IV. Images of the King. The Royal Persona as an Instrument of Public Policy. V. The Development of a Single National Image; cf. DissAbstr 48/03 (Sept. 1987) 723-A.